Design and Implementation of High-Precision Panel for Multichannel Micro-Flow Gas Monitoring in Oil Exploitation - Weilun Tang; Jian Liu; Yangjie Deng; Junli Yi; Yuchen Lu (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
Gas leakage is a common occurrence in crude oil exploitation, and may cause devastating effects or at least put the health of workers at stake if not managed properly. To address this issue, a type of high-precision panel for multichannel micro-flow gas monitoring was proposed in this paper, which can be applied to a range of scenarios including the monitoring of gas leakage in oil exploitation. Different channels for gas-flow sensors are provided on the panel, to monitor the gas flow in multiple places at the same time. The menu is enhanced with a multilevel design, which makes it possible for the functions to be customized. The research method of this paper followed these procedures: First, hardware design was illustrated. Next, the software solution was specified in the paper. Finally, based on theoretical analysis, laboratory experiments were successfully carried out, which demonstrated that the performance of this design was in line with our scheme. Overall, this design can help conduct early warning in the case of gas leakage and remind the operators to take timely response, which can significantly ensure the safety of crude oil exploitation.